Efficacy and Safety of Bintrafusp Alfa, a Bifunctional Fusion Protein Targeting Transforming Growth Factor-β and Programmed Death-Ligand 1, Plus Chemotherapy in Patients With Stage IV NSCLC - Christian Rolfo, MD, PhD; Laurent Greillier, MD, PhD; Remi Veillon, MD, PhD; Firas Badin, MD, MBA; Francois Ghiringhelli, MD, PhD; Nicolas Isambert, MD, PhD; Astrid Paulus, MD, PhD; Surendra Pal Chaudhary, MD; Yulia Vugmeyster, PhD; Masashi Sato, MSc; Sandrine Hiret, MD, PhD (JTO Clinical and Research Reports)
Introduction: In a phase 1 study, bintrafusp alfa was found to have an encouraging clinical activity in patients with previously treated advanced NSCLC. This study evaluated the safety and efficacy of bintrafusp alfa with chemotherapy in patients with stage IV NSCLC regardless of the programmed death-ligand 1 (PD-L1) expression status. Methods: In this open-label, phase 1b/2 study (NCT03840915), eligible patients were assigned to one of four cohorts. Patients with previously untreated metastatic NSCLC (cohorts A, B, and C) received bintrafusp alfa with chemotherapy as first-line treatment, whereas patients whose disease progressed on previous treatment with programmed cell death protein 1 or PD-L1 inhibitors (cohort D) received bintrafusp alfa with chemotherapy as second-line treatment. The primary objective of this study was to evaluate the safety and tolerability of bintrafusp alfa with chemotherapy. Results: Four serious and one nonserious treatment-emergent adverse events were considered dose-limiting toxicities, none of which were assessed as related to bintrafusp alfa by the investigator. Any-grade bintrafusp alfa-related adverse events occurred in 20.7% of patients in cohorts A+B+C and in 16.7% of patients in cohort D. Keratoacanthoma was the most common transforming growth factor-β inhibition-mediated skin lesion (cohorts A+B+C: 12.1% and cohort D: 8.3%). In cohorts A+B+C, the overall response rate was 48.3%, and in patients with PD-L1 tumor proportion score of more than or equal to 50.0%, it was 71.4%. On the basis of an interim analysis, the data were considered mature, and no further analysis has been planned. Conclusion: Bintrafusp alfa with chemotherapy was found to have a manageable safety profile and encouraging clinical activity in patients with stage IV NSCLC.